2020
DOI: 10.1182/blood.2019000989
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis and non-hematologic disorders

Abstract: Clonal expansions of mutated hematopoietic cells, termed clonal hematopoiesis, are common in aging humans. One expected consequence of mutation-associated clonal hematopoiesis is an increased risk of hematologic cancers, which has now been shown in several studies. However, the hematopoietic stem cells that acquire these somatic mutations also give rise to mutated immune effector cells, such as monocytes, granulocytes, and lymphocytes. These effector cells can potentially influence many disease states, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 110 publications
3
112
1
Order By: Relevance
“…Although the mechanistic link between CH and this large number of various disorders remains to be elucidated, CHassociated inflammation appears as the overarching principle. Diverse mediators of innate and adaptive immunity have been described to be modulated by the occurrence of specific CH-associated somatic mutations [65,66]. Not only cellular components of the myeloid lineage like monocytes/macrophages [56,[67][68][69][70], mast cells [71], neutrophils [72], but also lymphatic cells [73][74][75][76][77] can exert altered function.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanistic link between CH and this large number of various disorders remains to be elucidated, CHassociated inflammation appears as the overarching principle. Diverse mediators of innate and adaptive immunity have been described to be modulated by the occurrence of specific CH-associated somatic mutations [65,66]. Not only cellular components of the myeloid lineage like monocytes/macrophages [56,[67][68][69][70], mast cells [71], neutrophils [72], but also lymphatic cells [73][74][75][76][77] can exert altered function.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that stress-induced repeated HSC activation can lead to DNA damage in HSCs eventually obliterating hematopoiesis in mice [ 54 ]. Regarding mutations the concept of clonal hematopoiesis has been developed which is associated to malignant and nonmalignant diseases [ 55 , 56 ]. Such clonally expanding stem/progenitor cells can affect the original stem cell pool, or even take over hematopoiesis completely in humans [ 57 ] eventually decreasing its heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…However, driver mutations in HSCs leading to CH may also give rise to overproduction of mutated immune effector cells, such as monocytes, granulocytes, and lymphocytes. These effector cells can potentially influence many disease states, especially those with a chronic inflammatory component [126], resulting in elevated disease risk. In polycythemia vera and essential thrombocytemia, blood diseases belonging to a rare type of CH with pathological manifestations [127], overproduction of erythrocytes and thrombocytes results in a highly increased incidence of thrombotic events [128].…”
Section: Distance To the Endosteum Proliferative Potential Predominance Of Myeloid Differentiation Bm Homing Mobilization By Cytokinesmentioning
confidence: 99%